(untitled) (Journal of the College of Basic Education, 2022)
Love is the secret of life and the path of eternal existence, and spinning poems are chants and hymns:an introduction:It’s amazing and life has meaning, flavor and continuityAnd with love he is expelledOn the universe joy and magic wondrousconfer fWith love, societies are built and people enjoy comfort, happiness and reassuranceEvil, hatred and envy are among the warm gardens of life. If it were not for love, no one would come close to anotherThere is no male from a female, and the universe is devastated, destroyed, and estranged, with affection and loveFriendship and tenderness form families, and every pet lives in a pet. Love was born with a person to beHelp him to expel hatred, hatred and rancor, so he built civilizations and societies lasted strongand knit.Man described this relationship with spinning poems that were full of kindness and tendernessFriendship and happiness.Thus, Arab poets touched on this poetic purpose and excelled in it with great creativity